The Novel in Its Crisis of Globalization. - Cotoi, Amalia (Metacritic Journal for Comparative Studies & Theory, 2024)
Fredric Jameson's book "Inventions of a Present: The Novel in Its Crisis of Globalization" explores the intersection of literature, culture, and politics through a collection of essays on various novels. Jameson aims to reconcile content and form in literature, emphasizing the historical context and societal commentary embedded in novels. The book critiques traditional literary frameworks and advocates for a dynamic understanding of the novel as an intervention in the social sphere. While Jameson's analysis is rooted in Marxist theory, he also delves into the complexities of realism, modernism, and postmodernism in literature, challenging conventional boundaries and exploring the evolving nature of storytelling.